2012
DOI: 10.1007/s11120-011-9711-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Chloroflexus aurantiacus strain J-10-fl proteomes of cells grown chemoheterotrophically and photoheterotrophically

Abstract: Chloroflexus aurantiacus J-10-fl is a thermophilic green bacterium, a filamentous anoxygenic phototroph, and the model organism of the phylum Chloroflexi. We applied high-throughput, liquid chromatography-mass spectrometry in a global quantitative proteomics investigation of C. aurantiacus cells grown under oxic (chemoorganoheterotrophically) and anoxic (photoorganoheterotrophically) redox states. Our global analysis identified 13,524 high-confidence peptides that matched to 1,286 annotated proteins, 242 of wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 59 publications
(107 reference statements)
0
17
0
Order By: Relevance
“…switch from oxygenic photosynthesis to respiration and then fermentation (Nold and Ward, 1996, Steunou et al, 2006, Jensen et al, 2011. Other genes in the 'night pattern' cluster included csmC, encoding another GSB-specific chlorosome envelope protein ; pucC, whose product has various roles in photosynthesis (Tichy et al, 1991;Steunou et al, 2004;Jaschke et al, 2008); and genes neighboring csmA and csmC, whose probable functioning in photosynthesis is suggested by these and other data (Cao et al, 2012;Garcia Costas et al, 2012;Supplementary Figure 2). Assuming that translation continues in 'Ca.…”
Section: Photosynthesismentioning
confidence: 86%
“…switch from oxygenic photosynthesis to respiration and then fermentation (Nold and Ward, 1996, Steunou et al, 2006, Jensen et al, 2011. Other genes in the 'night pattern' cluster included csmC, encoding another GSB-specific chlorosome envelope protein ; pucC, whose product has various roles in photosynthesis (Tichy et al, 1991;Steunou et al, 2004;Jaschke et al, 2008); and genes neighboring csmA and csmC, whose probable functioning in photosynthesis is suggested by these and other data (Cao et al, 2012;Garcia Costas et al, 2012;Supplementary Figure 2). Assuming that translation continues in 'Ca.…”
Section: Photosynthesismentioning
confidence: 86%
“…These proteins were hypothesized to function during phototrophic (AurA) and respiratory (AurB) electron transfer, respectively (Lee et al, 2009). Contrary to these predictions, a recent proteomic analysis of C. aurantiacus OK-70-fl revealed that peptides corresponding to AurA were more abundant in cultures grown under dark oxic conditions than when grown photoheterotrophically, while peptides from AurB showed higher abundance during photoheterotrophic growth (Cao et al, 2012). The transcript levels for the aurA and aurB genes of Chloroflexus spp.…”
Section: Electron Transport Complexesmentioning
confidence: 94%
“…Genomes of Chloroflexus spp. contain paralogous genes encoding the soluble electron carrier, auracyanin (McManus et al, 1992;van Driessche et al, 1999;Tsukatani et al, 2007;Cao et al 2012), and both Chloroflexus and Roseiflexus spp. contain paralogs of some of the major enzyme complexes involved in the electron transport chain, namely NADH:menaquinone oxidoreductase (Complex I; van der Meer et al, 2010;Tang et al, 2011), and Alternative Complex III (ACIII; Yanyushin et al, 2005;Gao et al, 2009).…”
Section: Electron Transport Complexesmentioning
confidence: 99%
See 2 more Smart Citations